Pemeriksaan Kadar Hemoglobin, Pemberian Tablet Fe dan Penyuluhan Tentang Anemia serta Pencegehannya pada Siswi SMA Datuk Batu Hampar Pekanbaru - Arnila Melina; Inggrit Anggraini; Supriadi Supriadi; Fahmi Novriandi; Siska Silviana; Evy Eryta; Sabrina Hayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Anemia is a condition where the number of red blood cells or the concentration of hemoglobin in them is lower than normal. This disease mainly affects women and children. Anemia is classified into 3 parts based on the Hb value, namely mild, moderate and severe. Of these three categories, anemia is most prevalent in adolescents and pregnant women with productive age of 15-49 years in 124 countries included in WHO. The method used in conducting community service by using a preliminary survey conducted at Datuk Batu Hampar High School Pekanbaru, then conducted interviews with female students about their knowledge of anemia and continued with Hemoglobin checks and counseling about anemia. From the Hemoglobin examination on 30 female students, 5 were found with symptoms of anemia.